Experimentalism In Hilda Doolittle's HERmione - Ibrahim, Juan Abdullah (Al-Adab Journal, 2015)
Hilda Doolittle (1886-1946) is an American poet, novelist and translator, generally called H.D. In her Autobiographical novel, HERmione unpublished until 1981, Hilda presents her experimental work in which she imposes a narrative form upon her fictionalized accounts of her tangled personal relations. It is a novel about well-known literary people and a story of forbidden desires, it invokes the patterns of the genre to examine the interpretation of sexuality and textuality in a narrative of development. HER is a literary suppressed, figuratively repressed story of origins whose private telling was essential to public retellings of how Hilda Doolittle became H.D. Hilda Doolittle's novel is characterized by being revolutionary , experimenting through repetition of names of people , disguised through specific literary language attacking the patriarchal mode of a stern father and a passive , submissive mother. Lights are shed through a psychological approach on the writers traumatic experiences as a result of war consequences on one hand and personal , agonic experiences due to her doubt about her Sexuality being torn between lesbian desire and heterosexual feeling towards a man she loved but was not able to marry. H.D.'s aim is to create a change in women's state from the conventional treatment of women as an "object" to a new "subject" worthy of description getting benefit from Sigmund Freud's psychological analysis of Hilda Doolittle's character when she was sick. Being an effective imagist and a lover of Arts, she creates a new literary movement depending on common speech and freedom in choosing subjects in a daring style. Since the subject of the novel is about the psychological issues of women's identity problems , feminist critics views like Susan Stanford Friedman , Rachel Blau Duplessis and Helen Cixous's theory of Psychology are taken into consideration in this research